(untitled) (Journal of Educational Sciences, 2025)
The article examines current issues related to the use of artificial intelligence (AI) in education. It analyzes its strengths and weaknesses, as well as potential threats and risks that may arise in the learning process if technologies are used improperly. It is emphasized that before integrating AI into the educational process, preparatory steps must be taken, in particular ensuring the professional development of teachers. Special attention is given to the importance of training educators to work with AI correctly and responsibly. The article also describes possible barriers and challenges that the education system may face when integrating new digital solutions. The best artificial intelligence neural networks recommended for educational purposes are presented and characterized. An example of a curriculum on the use of AI in both school and university practice is provided. The article highlights that a modern teacher should not only master their subject but also be able to adapt to the requirements of the digital age. AI is both a challenge and an opportunity to make education more high-quality, accessible, and individualized. In the practical part of the research, a survey was conducted involving 40 educators: 20 school teachers and 20 university lecturers. Based on a comparison of the survey results, professional development programs were designed for school teachers and university lecturers. Each program is designed for 36 hours. Key words: digital technologies, artificial intelligence, neural networks, chatbots, curriculum.